Decoding the complete arsenal for cellulose and hemicellulose deconstruction in the highly efficient cellulose decomposer Paenibacillus O199 - López-Mondéjar, Rubén; Zühlke, Daniela; Větrovský, Tomáš; Becher, Dörte; Riedel, Katharina; Baldrian, Petr (Biotechnology for biofuels, 2016)
BACKGROUND: The search for new enzymes and microbial strains to degrade plant biomass is one of the most important strategies for improving the conversion processes in the production of environment-friendly chemicals and biofuels. In this study, we report a new Paenibacillus isolate, O199, which showed the highest efficiency for cellulose deconstruction in a screen of environmental isolates. Here, we provide a detailed description of the complex multi-component O199 enzymatic system involved in the degradation of lignocellulose. RESULTS: We examined the genome and the proteome of O199 grown on complex lignocellulose (wheat straw) and on microcrystalline cellulose. The genome contained 476 genes with domains assigned to carbohydrate-active enzyme (CAZyme) families, including 100 genes coding for glycosyl hydrolases (GHs) putatively involved in cellulose and hemicellulose degradation. Moreover, 31 % of these CAZymes were expressed on cellulose and 29 % on wheat straw. Proteomic analyses also revealed a complex and complete set of enzymes for deconstruction of cellulose (at least 22 proteins, including 4 endocellulases, 2 exocellulases, 2 cellobiohydrolases and 2 β-glucosidases) and hemicellulose (at least 28 proteins, including 5 endoxylanases, 1 β-xylosidase, 2 xyloglucanases, 2 endomannanases, 2 licheninases and 1 endo-β-1,3(4)-glucanase). Most of these proteins were secreted extracellularly and had numerous carbohydrate-binding domains (CBMs). In addition, O199 also secreted a high number of substrate-binding proteins (SBPs), including at least 42 proteins binding carbohydrates. Interestingly, both plant lignocellulose and crystalline cellulose triggered the production of a wide array of hydrolytic proteins, including cellulases, hemicellulases, and other GHs. CONCLUSIONS: Our data provide an in-depth analysis of the complex and complete set of enzymes and accessory non-catalytic proteins-GHs, CBMs, transporters, and SBPs-implicated in the high cellulolytic capacity shown by this bacterial strain. The large diversity of hydrolytic enzymes and the extracellular secretion of most of them supports the use of Paenibacillus O199 as a candidate for second-generation technologies using paper or lignocellulosic agricultural wastes.
Keywords: Paenibacillus; CAZyme; Glycosyl hydrolase; Cellulose; Plant biomass; Hemicellulose